The impact of Project-based Learning on senior high school students’ academic performance - Rumfot, Sumarni; Sahib, Abdul; Oka, Anak Agung; Ramadhan, Iwan; Anshoriyah, Sofiyatul (Journal of Educational Management and Instruction (JEMIN), 2025)
This study aims to examine the effect of the Project-Based Learning (PjBL) method on the academic performance of senior high school students. With the increasing demand for innovative teaching methods to enhance student engagement and achievement, this research focuses on a public senior high school in Jakarta, Indonesia. The research utilized a qualitative case study approach involving 11 students and 5 teachers as participants. Data were collected through in-depth interviews, classroom observations, and document analysis. Thematic analysis was applied to identify key patterns and insights. The findings revealed that the PjBL method significantly fostered students' critical thinking skills, collaboration, and intrinsic motivation, all of which contributed to improved academic performance. Teachers' involvement in project design, as well as the availability of adequate learning resources, were identified as crucial factors in the successful implementation of PjBL. This study suggests that when implemented with thoughtful planning and sufficient support, PjBL can be a highly effective approach for enhancing student outcomes. The research contributes to the growing body of evidence supporting the integration of PjBL in the classroom and underscores its potential as a strategy to address academic challenges in senior high schools.